1998
DOI: 10.1111/j.1540-8167.1998.tb00886.x
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Macroreentry Involving the Myocardium of the Coronary Sinus: A Unique Mechanism for Atypical Flutter

Abstract: Atrial flutter involving either clockwise or counterclockwise rotation around the tricuspid annulus utilizing the subeustachian isthmus has been well described. However, macroreentrant atrial circuits in atypical atrial flutter in patients who have not undergone previous surgery or without atrial disease are not well defined. We describe a patient without structural heart disease who presented with an atrial macroreentrant rhythm. Entrainment mapping demonstrated a critical isthmus within the coronary sinus. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
77
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(81 citation statements)
references
References 17 publications
3
77
1
Order By: Relevance
“…21 Multiple disparate con- nections between the right and left atria may allow for the substrate for biatrial flutter, entering the left atrium from the CS, travelling around the pulmonary veins to Bachmann's bundle, reentering the right atrium over this bundle, and travelling down the right atrial septum to link again with the CS, as suggested by Olgin et al 22 …”
Section: Discussionmentioning
confidence: 84%
“…21 Multiple disparate con- nections between the right and left atria may allow for the substrate for biatrial flutter, entering the left atrium from the CS, travelling around the pulmonary veins to Bachmann's bundle, reentering the right atrium over this bundle, and travelling down the right atrial septum to link again with the CS, as suggested by Olgin et al 22 …”
Section: Discussionmentioning
confidence: 84%
“…[3][4][5][6] Focal atrial tachycardias and focal AF originating in the CS musculature have been reported, [7][8][9][10] and this musculature also contributes to a macroreentrant circuit that generates left atrial flutter.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] More recently, attention has been directed to the elucidation and cure of patients with left atrial (LA) circuits. [7][8][9] Olgin et al 9 first described a reentrant circuit involving the musculature of the coronary sinus (CS) that was amenable to ablation of the muscle at the CS ostium. A variety of LA circuits that occurred in patients with organic cardiac disease that were associated with large "silent" areas over the posterior LA have been described.…”
mentioning
confidence: 99%